Principles of Public Management in Scandinavian Countries: A Theoretical Assessment - Jan Ole Vanebo; Jon Aarum Andersen (Central European Public Administration Review)
strengthen leadership practices in the public sector. The policy documents ”Code for Chief Executive Excellence” (Denmark) and ”Leadership in Norway’s Civil Service” pertain to how the public sector ought to be managed. This article addresses two problems concerning these documents. To what degree does New Public Management (NPM) influence them? To what degree does management and leadership theory and research support the principles proposed by these documents? This article concludes that NPM has had a significant impact on public management in the Scandinavian countries. The policy documents are based on leadership research and are in accordance with mainstream management theory. The idea of formulating a principle of management that would characterize the classical contributions is also evident in these documents.